Tuberculous Otitis Media: a case report of hearing impairment in developing country - Giovanni Reynaldo; Bernadina Chyntia Carsantiningrum; Harim Priyono (PERHATI-KL, 2020)
ABSTRACTBackground: Tuberculosis is one of major health problems in developing countries, especially extrapulmonary tuberculosis. Tuberculous otitis media (TOM) is one of extrapulmonary manifestations which is a rare phenomenon characterized by painless otorrhea, insidious onset of ear discharge, multiple perforations in the tympanic membrane, and pale granulation tissues in middle ear cleft. Purpose: Reporting one rare case of TOM. Case Report: A 58-year-old male came with painless otorrhea and recurrent hearing impairment. Tympanomastoidectomy was carried out to repair the tympanic membrane, to cleanse the secret from the middle ear, and to obtain sample for biopsy. Histopathological examination showed necrotizing granuloma which contained mycobacterium tuberculosis infection. Medical treatment was administration of anti tuberculosis drugs. Clinical Question: How to establish TOM diagnosis? Review Method: Searching for literature evidence through Google Scholar. Result: The search obtained 20 journals which in accordance with the inclusion and exclusion criteria. There were similarities on clinical and therapeutic symptoms with this reported case. Discussion: In the reported case, the probable pathophysiology was bacterial aspiration through the Eustachian tube, which was just diagnosed during pre-operative screening. There was no apparent pulmonary tuberculosis symptom. Diagnosis TOM with mastoiditis was difficult, it required high skilled accuracy. Conclusion: TOM is a rare manifestation of extrapulmonary tuberculosis. High suspicion of TOM is needed in patients who did not respond to standard treatment. Treatment includes administration of anti-tubercular drugs, and surgical procedure to cleanse the secretion and granulation tissues. Permanent hearing loss can occur in cases of delayed diagnosis. ABSTRAKLatar belakang: Tuberkulosis merupakan masalah kesehatan di negara berkembang, terutama tuberkulosis ekstra pulmonal. Otitis media tuberkulosa (OMT) merupakan salah satu manifestasi tuberkulosis ekstra pulmonal yang jarang terjadi dan ditandai dengan gejala klinis berupa keluar cairan dari telinga tanpa disertai rasa nyeri, onset penyakit berjalan lambat, terdapat perforasi multipel pada membran timpani, dan jaringan granulasi pucat di rongga telinga tengah. Tujuan: Melaporkan satu kasus OMT yang jarang ditemukan. Laporan Kasus: Seorang laki-laki 58 tahun datang dengan keluhan keluar cairan dari telinga tanpa disertai rasa nyeri, dan ada gangguan pendengaran berulang. Pada pasien dilakukan tindakan bedah timpanomastoidektomi untuk memperbaiki membran timpani yang rusak, membersihkan sekret, dan melakukan biopsi jaringan. Hasil pemeriksaan histopatologi didapati jaringan granuloma nekrotikans yang menunjukkan adanya infeksi Mycobacterium tuberculosis. Diberikan terapi medikamentosa obat anti tuberkulosa. Pertanyaan Klinis: Bagaimana menegakkan diagnosa OMT? Telaah literatur: Penelusuran bukti kepustakaan melalui Google Scholar. Hasil: Penelusuran menghasilkan 20 jurnal yang memenuhi kriteria inklusi dan eksklusi dan memiliki kesamaan gejala klinis dan terapi dengan kasus yang dilaporkan. Diskusi: Pada kasus ini kemungkinan patofisologinya adalah aspirasi bakteri melalui tuba eustachius, dan OMT baru terdiagnosis saat dilakukan skrining pra-operasi. Tidak didapati gejala tuberkulosis paru. Diagnosis OMT dengan mastoiditis cukup sulit, diperlukan ketelitian yang tinggi. Kesimpulan: OMT merupakan manifestasi tuberkulosis ekstra pulmonal yang jarang terjadi. Perlu kecurigaan yang tinggi adanya OMT pada pasien yang tidak responsif terhadap pengobatan standar. Penatalaksanaan meliputi pemberian obat anti tuberkulosa, dan tindakan bedah untuk mengeluarkan dan membersihkan sekret dan jaringan granulasi. Gangguan pendengaran permanen bisa terjadi pada kasus yang penatalaksaannya terlambat.